Max Plus Algebra and Petri Net Application on Scheduling of Ship Engine Component’s Spare Part Ordering - Farah Azizah; Subiono Subiono ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2018)
Shipping company is a company that runs its business by operating the ships or other businesses that are closely related to the ship. A ship has a main engine and some auxiliary engines to support the ship performance. It needs to do maintenance of engines so that the ship can operate properly. This engine maintenance is replacement of the old engine components with the new ones if the running hours of the components are over. Therefore, in the ship, the spare parts must always be available at least one for each engine component. During this time, the company has experienced a difficulty in determining the time of spare part ordering. When the running hours of engine components are over, the spare parts were not yet available. Then, Petri Net and Max Plus Algebra model will be built to schedule the ordering of ship engine component’s spare part based on the ordering flow and the running hours of engine components. The Petri Net based on the Max Plus Algebra obtains maximum time to order the spare part so that it produces the ship engine component’s spare part ordering schedule in running hour form and date. Therefore, spare part of each ship engine component is always available so that the installation can be timely and never be late.